The role of financial education of members of the public in the legal mandate of the central bank of Lesotho - Kabai, Thobeli (My University, 2018)
This paper examines whether there is any role for financial education of the members of the public in the legal mandate of the Central Bank of Lesotho. The traditional functions of the central banks have been discussed to see first whether Central Bank of Lesotho performs functions similar to those of its sister banks. All the statutes that enshrine the functions of the central bank are analysed and interpreted in order to conclude whether and how financial education of the members of public forms part of the legal mandate. Conclusions and recommendations on how best to address financial education in Lesotho are made at the end of this report.
A research report submitted to the Faculty of Commerce, Law and Management of the University of the Witwatersrand, in partial fulfillment of the requirements of the degree Master of Laws in Labour Law, 2018
Keywords: Financial institutions, International--Law and legislation; Financial institutions--Law and legislation